Kesiapsiagaan Petugas Kesehatan di Rumah Sakit terhadap Bencana Gempa: Systematic Literature Review - Ng.Susanti, I Gusti Ayu Ng.Susanti; Medriono, Medriono; Fadli, Moh.; Sudirman, Sudirman; Yani, Ahmad (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Earthquakes have a significant impact on healthcare services, making the preparedness of healthcare workers in hospitals critically important. This study aims to examine the preparedness of healthcare workers in facing earthquake disasters through a literature review using the PRISMA approach. A total of seven articles were analyzed, selected based on inclusion criteria from 2020–2026 and their relevance to the research topic. The findings indicate that preparedness is influenced by individual factors (knowledge, disaster literacy, and psychological readiness), organizational factors (training, simulation, and leadership), and system factors (infrastructure, resources, and technology). Several challenges remain, including limited training and inadequate readiness of healthcare facilities. In conclusion, the preparedness of healthcare workers in hospitals for earthquake disasters needs to be improved through an integrated approach involving individual, organizational, and system factors.